Computational modeling and simulation of spall fracture in polycrystalline solids by an atomistic-based interfacial zone model. (July 2015) - Lin, Liqiang; Zeng, Xiaowei
Highlights: Modeling grain boundaries by interfacial zone model. High-speed impact induced spall fracture in polycrystalline materials. Investigation of intergranular/transgranular fracture transition under impact loading. Investigating how grain size, crystal lattice orientation, and impact speed affect spall strength. Abstract: The focus of this work is to investigate spall fracture in polycrystalline materials under high-speed impact loading by using an atomistic-based interfacial zone model. We illustrate that for polycrystalline materials, increases in the potential energy ratio between grain boundaries and grains could cause a fracture transition from intergranular to transgranular mode. We also found out that the spall strength increases when there is a fracture transition from intergranular to transgranular. In addition, analysis of grain size, crystal lattice orientation and impact speed reveals that the spall strength increases as grain size or impact speed increases.